Systematic Review : The Effect of Massage Effleurage on Dysmenorrhea - Niken Bayu Argaheni (Journal of Ners and Midwifery, 2021)
Introduction: In Indonesia, the incidence of dysmenorrhea is 64.25% consisting of primary dysmenorrhea amounted to 54.89% and secondary dysmenorrhea of 9.36%. Some women experienced menstrual pain or cramps, also known as dysmenorrhea. The purpose of this research was to find out the effect of abdominal massage effleurage on decreasing the pain scale of primary dysmenorrhea. Method: Systematic review using the database: Google Scholar. The search results that meet the criteria were then analyzed for articles. Result: Primary dysmenorrhea pain could be relieved by massage techniques such as abdominal effleurage massage. Conclusion: To deal with dysmenorrhea pain, it is advisable for young women not to consume it immediately pharmacological drugs but using massage therapy such as massage effleurage abdomen.